1992
DOI: 10.1044/1058-0360.0103.29
|View full text |Cite
|
Sign up to set email alerts
|

Evoking [r] Using Visual Feedback

Abstract: An adult who was not able to produce singleton consonantal [r] or any of the r-colored vowels correctly (although he could produce some consonant clusters containing [r]) was enrolled in a treatment program for remediation of these sounds. When, after 17 therapy sessions, he was still unable to produce any of these sounds accurately, a real-time speech spectrograph was introduced to provide visual feedback. Within two sessions, the client was able to produce [] correctly. We were then able to use his productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 15 publications
0
35
0
Order By: Relevance
“…For example, mirrors are often used to help patients see their own lip or jaw movements. Using the acoustic signal, spectral feedback has also been used to teach participants with speech disorders to achieve proper formant structure for vowels or rhotics (McAllister Byun & Hitchcock, 2012;Shuster, Ruscello, & Smith, 1992;Shuster, Ruscello, & Toth, 1995).…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…For example, mirrors are often used to help patients see their own lip or jaw movements. Using the acoustic signal, spectral feedback has also been used to teach participants with speech disorders to achieve proper formant structure for vowels or rhotics (McAllister Byun & Hitchcock, 2012;Shuster, Ruscello, & Smith, 1992;Shuster, Ruscello, & Toth, 1995).…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…Fletcher et al, 1991) or real-time spectral or spectrographic displays (e.g. McAllister Byun & Hitchcock, 2012; Shuster et al, 1992, 1995). The present study used ultrasound imaging as the mechanism of biofeedback delivery.…”
Section: Biofeedback Interventionmentioning
confidence: 99%
“…These persistent errors pose a particular challenge for speech-language pathologists, with the result that many clients are discharged with residual errors uncorrected (Ruscello, 1995). Recent research has provided increasingly strong evidence that visual biofeedback intervention can succeed in eliciting correct production from children whose speech errors have not responded to other forms of treatment (Adler-Bock, Bernhardt, Gick, & Bacsfalvi, 2007; McAllister Byun & Hitchcock, 2012; Modha, Bernhardt, Church, & Bacsfalvi, 2008; Preston, Brick, & Landi, 2013; Ruscello, 1995; Shuster, Ruscello, & Smith, 1992; Shuster, Ruscello, & Toth, 1995). However, many of these studies have identified a limitation of biofeedback treatment: generalisation of gains made in treatment is not automatic, with some participants remaining largely dependent on the continued availability of visual feedback to achieve correct production of their speech sound targets (Fletcher, Dagenais, & Critz-Crosby, 1991; Gibbon & Paterson, 2006; McAllister Byun & Hitchcock, 2012; McAllister Byun, Hitchcock, & Swartz, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Of note, HCI research [11,19] and behavioral research [2,38] have used computer solutions in the context of speech therapy and communication. Within the ASD community, Hoque has explored sentence practice with higher functioning individuals with ASD through the use of games [18].…”
Section: Technology Research On Autism and Speech Delaysmentioning
confidence: 99%